Phytochemicals Composition and Anti-bacterial Activity of Methanol Leaves Extract of Vernonia amygdalina - Galadima, Abdulganiyu Mohammed; Chidimma, Amaechi Jessica; Abubakar, Ibrahim; Ibrahim, Shehu; Said, Said Sani (Biology, Medicine, & Natural Product Chemistry, 2025)
Bacterial infections have been a major health challenge associated with high morbidity and mortality rates. Plants and their metabolite constituents are important in local therapies and drug synthesis. This study aimed to evaluate the phytochemical composition and anti-bacterial activity of the methanol leaves extract of Vernonia amygdalina. Phytochemicals in the extract were estimated using standard analytical methods. The antibacterial activity test of the plant extract was carried out using the agar diffusion method. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined using the tube dilution method and sub-culturing technique, respectively. The extract contains significant amount of alkaloids (47.44 %), flavonoids (16.60 %), tannins (4.35 %), saponins (12.28 %), steroids (0.86%), and glycosides (0.18%). The extract exhibited significant (p < 0.005) inhibitory effect against Staphylococcus aureus, Streptococcus agalactiae, and Lactobacillus rhamnosus isolates with MIC and MBC values of 12.45 and 25.51 mg/mL, 22.03 and 44.84 mg/mL, and 31.64 and 63.95 mg/mL, respectively. The methanol leaves extract of Vernonia amygdalina demonstrated an inhibitory effect against Staphylococcus aureus, Streptococcus agalactiae, and Lactobacillus rhamnosus isolates with low minimum inhibitory concentration values.